\(\displaystyle{1}={1}^{{3}}\because{1}\cdot{1}\cdot{1}={1}\)

\(\displaystyle{8}={2}^{{3}}\because{2}\cdot{2}\cdot{2}={8}\)

\(\displaystyle{27}={3}^{{3}}\because{3}\cdot{3}\cdot{3}={27}\)

\(\displaystyle{64}={4}^{{3}}\because{4}\cdot{4}\cdot{4}={64}\)

\(\displaystyle{125}={5}^{{3}}\because{5}\cdot{5}\cdot{5}={125}\)

\(\displaystyle{8}={2}^{{3}}\because{2}\cdot{2}\cdot{2}={8}\)

\(\displaystyle{27}={3}^{{3}}\because{3}\cdot{3}\cdot{3}={27}\)

\(\displaystyle{64}={4}^{{3}}\because{4}\cdot{4}\cdot{4}={64}\)

\(\displaystyle{125}={5}^{{3}}\because{5}\cdot{5}\cdot{5}={125}\)